Implications to secure mineral supply for clean energy technologies for developing countries: A fuzzy based risk analysis for mining projects. (15th July 2022) - Jiskani, Izhar Mithal; Moreno-Cabezali, Belen Maria; Ur Rehman, Atta; Fernandez-Crehuet, Jose Maria; Uddin, Salah
Abstract: Cleaner energy production relies on the sustainable supply of critical minerals. Ensuring a constant supply of these minerals is integral to cleaner energy initiatives. The majority of global green energy initiatives rely on minerals mined in developing countries. However, there are challenges in fulfilling the ever growing demands to supply minerals in an economically viable, socially beneficial, and environmentally responsible manner, and these can multiply as a result of delays or stoppages caused by various risks affiliated with the mining industry. This can drastically affect the supply chain of minerals and other dependent components in the overall process to generate cleaner energy. Therefore, identification, prioritization, and future remediation plans for probable risks related to the mineral supply chain are necessary. This work identifies 39 different risks characterized in seven major groups: economic and financial risks, environmental and climate, health and safety, management, political and legal, social, and technical and operational. The probable risks associated with mining projects are prioritized using a fuzzy logic-based methodology, and the remediation plans are discussed to address the challenges upfront before their occurrence. Results reveal that the technical and operational and economic and financial risks take precedence over those related to political and legal, social, environmental and climate, health and safety, and managerial groups. This research can help policymakers in developing strategies to mitigate potential risks and lessen their influence on the supply chain of critical minerals supply required for cleaner production.